Vertebral Fracture Assessment Increases Use of Pharmacologic Therapy for Fracture Prevention in Clinical Practice. (10th September 2019) - Schousboe, John T; Lix, Lisa M; Morin, Suzanne N; Derkatch, Sheldon; Bryanton, Mark; Alhrbi, Mashael; Leslie, William D
ABSTRACT: The impact of vertebral fracture assessment (VFA) on lateral spine images in clinical practice on subsequent patient use of fracture prevention medication is unknown. Our objective was to determine the association of prevalent vertebral fracture identified on bone density lateral spine images (positive VFA) with subsequent use of fracture prevention therapy in usual clinical practice, using the Manitoba Bone Density Program database prospective observational cohort. Since 2010, targeted VFA imaging has been done at the time of bone densitometry in Manitoba for 21% of women and men meeting criteria based on age, bone mineral density (BMD), height loss, and glucocorticoid use. Among 6652 treatment‐naive individuals with at least 90 days follow‐up who had VFA imaging, 923 (13.9%) had one or more definite vertebral fractures identified using a modified algorithm‐based qualitative (ABQ) method. For those with a positive VFA, their bone density reports stated the patient was at high risk of subsequent fracture and qualified for fracture prevention therapy. Subsequent osteoporosis treatment initiated within the next 12 months was identified using population‐based pharmacy data. Logistic regression models were used to estimate the association of positive VFA with subsequent prescription (Rx), compared to negative VFA. Fracture prevention medication was started by 2127 (32%) individuals, 52.3% with positive versus 28.4% with negative VFA ( p value <0.001). This association was substantially stronger in those designated (before VFA results were known) to have low or moderate fracture risk compared to high fracture risk (interaction p value <0.001), and in those with osteopenia (OR 4.51; 95% CI, 3.48 to 5.85) compared to those with osteoporosis by BMD criteria (OR 1.72; 95% CI, 1.43 to 2.08, interaction p value <0.001). Targeted VFA imaging at the time of bone densitometry substantially improves identification of those at high fracture risk and fracture prevention medication use among those with prevalent vertebral fracture. © 2019 American Society for Bone and Mineral Research. © 2019 American Society for Bone and Mineral Research.